Stress tests for public service resilience : introducing the possible-worlds thinking - Rajala, Tomi; Jalonen, Harri (Taylor & Francis, 2022)
Tackling the COVID-19 pandemic and reverting to normal life and services requires resilience. This qualitative case study aims to help public sector managers understand service resilience and its accompanying breaking points by proposing a scenario planning model that tests resilience by applying possible-worlds thinking to public services. The proposed scenario planning model is based on empirical evidence showing how service design incorporated assumptions that became inaccurate in the pandemic, and how these inaccurate assumptions created pressures for change in the service design and production. The model we propose can help public managers apply such stress tests in practice.
Keywords: public service organization; scenario planning; public service management; strategic planning; resilience; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|